Migration and its relation to value changes - Al Salem, Amnah Ali Hussein (Arab Journal for Sciences and Research Publishing, 2015)
The present study addressed the issue of immigration value and the changes in the Iraqi immigrants abroad also dealt with the motives of migration from Iraq to other countries and see how adaptation of migrants in host countries and what most of the problems from which they suffer, the study touched on the migration across different eras and how they were motivated migration every era starting from prehistoric times through the ancient Ages and Islamic eras end of the modern era. It is known that the environment influences individuals significant impact and possibly pay people to change their habits and traditions, that the importance of the study of values ​​and knowledge of the extent of the changes caused by immigration and the extent of the change in values ​​through these migrations and the extent of migrant families commitment to the values ​​and traditions of the native country of the problems that drive the search for knowledge moral reasons, the change in the migrant families and caused them to change.
Keywords: Migration; moral changes